2021
DOI: 10.1016/j.ijpx.2021.100099
|View full text |Cite
|
Sign up to set email alerts
|

Downstream processing of spray-dried ASD with hypromellose acetate succinate – Roller compaction and subsequent compression into high ASD load tablets

Abstract: Despite wide commercial application of hypromellose acetate succinate (HPMCAS) in spray-dried amorphous solid dispersion (ASD) drug products, little information is available in the references on downstream processing of spray-dried dispersions with HPMCAS. Poor flow and high dilution factor are a challenge in formulating spray-dried ASDs into tablets, leaving little space for other excipients facilitating binding and disintegration. Direct compression is not possible due to the poor powder flow of spray-dried … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 32 publications
0
5
0
Order By: Relevance
“…Rapid disintegration of a tablet into smaller particles is essential for fast release of the drug [ 8 , 12 ]. All tablets prepared in the experimental design disintegrated within one minute ( Table S5, Supplementary Materials ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Rapid disintegration of a tablet into smaller particles is essential for fast release of the drug [ 8 , 12 ]. All tablets prepared in the experimental design disintegrated within one minute ( Table S5, Supplementary Materials ).…”
Section: Resultsmentioning
confidence: 99%
“…Despite the considerable interest in ASD formulations, downstream processing studies for the development of ASD tablets are limited due to various challenges associated with the properties of ASDs [ 7 ]. In our previous study, we reported on the downstream processing of a spray-dried ASD of nifedipine using hypromellose acetate succinate (HPMCAS) as a carrier polymer [ 8 ]. However, the challenges faced in the downstream processing of ASDs prepared by spray drying are totally different from those encountered in the production of HME-based ASDs.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…6,14,15 Several commercial products are prepared as ASDs with HPMCAS, including telaprevir (Incivek, Vertex, US); ivacaftor (Kalydeco, Vertex, US); vemurafenib (Zelboraf, Roche, Switzerland); posaconazole (Noxafil, Merck, US); and apalutamide (Erleada, Janssen, US). 16−20 In contrast, HPMCP has been used less for commercial ASD formulations, with its use reported only for itraconazole (Lozanoc, Mayne Pharma, Australia) 16,18,21 and delamanid (DLM) (Deltyba, Otsuka, Japan). 22 Importantly, enteric polymers are un-ionized and insoluble in acidic environments, leading to reduced crystal growth inhibition effectiveness at low pH.…”
Section: Introductionmentioning
confidence: 99%
“…Amphiphilic, ionizable polymers, such as hydroxypropyl methylcellulose acetate succinate (HPMCAS), hydroxypropyl methylcellulose phthalate (HPMCP), Eudragit L100, and cellulose acetate phthalate, have been found to be effective at maintaining drug supersaturation and enhancing in vivo absorption. ,, Among these, HPMCP and HPMCAS have been noted to be good crystallization inhibitors for many drugs. ,, Several commercial products are prepared as ASDs with HPMCAS, including telaprevir (Incivek, Vertex, US); ivacaftor (Kalydeco, Vertex, US); vemurafenib (Zelboraf, Roche, Switzerland); posaconazole (Noxafil, Merck, US); and apalutamide (Erleada, Janssen, US). In contrast, HPMCP has been used less for commercial ASD formulations, with its use reported only for itraconazole (Lozanoc, Mayne Pharma, Australia) ,, and delamanid (DLM) (Deltyba, Otsuka, Japan) . Importantly, enteric polymers are un-ionized and insoluble in acidic environments, leading to reduced crystal growth inhibition effectiveness at low pH. , For example, HPMCAS (-LF grade) was found to be less effective at inhibiting the crystal growth of felodipine at a lower pH than at a higher pH .…”
Section: Introductionmentioning
confidence: 99%